Maintenance of the Bali Language in the Permas Oral Tradition in Mundeh Traditional Village Nyambu Village, Kediri District, Tabanan Regency - Sentana, Gek Diah (e-Journal of Linguistics; Vol 16 No 1 (2022): ejl-January, 2021)
The Permas oral tradition is the oral tradition of the Mundeh village community, Kediri sub-district, Tabanan district, Bali Province. This tradition is very unique, which only takes place during piodalan jelih at Pura Pesamuan, the traditional village of Mundeh. The Permas tradition was present as a conflict resolution, when Ratu Gede Disconnected returned to Mundeh. The Oral Permas tradition has become a medium for maintaining Balinese culture and language, for the Mundeh traditional village community, especially for children who become Jero Permas.   This study uses qualitative methods to find phenomena, circumstances and data about the Permas oral tradition. The primary data source is the Permas oral tradition, while the secondary data is a literature review related to the Permas oral tradition. The theory used is the theory of discourse, according to Van Dijk, this is in line with the opinion that every unit of discourse, both large and small, has a form as a certain structure. Discourse is created with a specific purpose, positive or negative as a function of maintaining a culture, especially the Balinese language. The results of this study are the verbal form of the Permas oral tradition and aspects of maintaining the Balinese language in the Permas Oral Tradition.